The Taste of Salt - Sammon, Dylan (Cuizine, 2025)
While depleting cod stocks, backroom politics, two world wars, an occasional natural disaster, and the unforgiving tug of modernity all contributed to the decline of Newfoundland’s outport villages, none of those factors could erase the rich culinary traditions that came from outport kitchens. What follows is a story that speaks to that decline, to the people who lived through it, and to the recipes they created. In 1970s Nebraska, rolling blackouts are causing disruptions in the local correctional facility’s execution schedule. Simply put, the electric chair won’t work if there’s no power. This breakdown plays to one death row inmate’s favour, however, as an institutional technicality allows him to get a different last meal for every night that he is due to be executed. The inmate’s name is Cupid Dawes, and his meal choices end up revealing a long-lost culture that (through taste) reignites his love of life and home and helps him come to terms with both his past and his present. Luckily for us, the local paper’s death-row correspondent is on hand to witness it all, even acting as a messenger between Cupid and the angry prison chef who must manage the inmate’s progressively more specific meal requests.